2006
DOI: 10.1016/s0929-6646(09)60283-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Berg Balance Scale in a Community-dwelling Elderly Resident Population in Taiwan

Abstract: The results of this study suggest that the internal consistency reliability, interrater reliability, and construct validity of the BBS are adequate for measuring balance in community-dwelling older adults. Among all items in the BBS, the tandem stance and one-legged stance are the most challenging items. Further study of their applicability for screening use in the community is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 47 publications
3
34
0
4
Order By: Relevance
“…The heterogeneity test of sensitivity and specificity shows X² = 59. 34 On the four studies found on BBS, one did not analyze the predictive validity, the other three studies obtained the combined sample size of 653 elderly individuals over 60 years old who were able to complete the Scale. Of these 329 elderly people reported a history of a retrospective or prospective fall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity test of sensitivity and specificity shows X² = 59. 34 On the four studies found on BBS, one did not analyze the predictive validity, the other three studies obtained the combined sample size of 653 elderly individuals over 60 years old who were able to complete the Scale. Of these 329 elderly people reported a history of a retrospective or prospective fall.…”
Section: Resultsmentioning
confidence: 99%
“…Studies point to a Cronbach's alpha ranging from 0.62 to 0.98; Sensitivity between 42% and 97%; Specificity between 26% and 92%; Cut point between 45 and 50 points (10,13,30,31,32,33,34,35,30,36,37,38,39) . Despite presenting a high alpha of Cronbach indicating a good internal consistency, as well as a good association between item-factor and the other factors, this does not guarantee a good internal consistency in the measurement of the postural control construct.…”
Section: Discussionmentioning
confidence: 99%
“…28 Pimentel e Schecer 29 demostraram também melhores médias de equilíbrio em idosos praticantes de atividades físicas (53,6 ± 3,7), quando comparados a idosos sedentários (47,7 ± 5,6). Embora a utilização da Escala de Equilíbrio de Berg seja largamente utilizada no meio científico, [30][31][32] diferenças entre a capacidade motora da amostra investigada e da população utilizada, no estudo de Myiamoto et al, 17 para a adaptação da Escala no Brasil, pode ter sido determinante para os resultados não demonstrarem diferenças entre os grupos no presente estudo. Ou seja, mesmo os idosos não treinados apresentavam uma condição física melhor que a população de pacientes do referido estudo, gerando pouca sensibilidade para encontrar diferenças entre os grupos de idosos treinados e não treinados.…”
Section: Correlação Entre Os Resultados Obtidos Em Testes Motores E Ounclassified
“…Além disso, grande parte da intervenção foi realizada em posição vertical, melhorando assim o equilíbrio das idosas (WANG et al, 2006 (CINDY, 2008;DEUTSCH et al, 2008;GRAVES et al, 2008;CLARK e KRAEMER, 2009). Além disso, a participação em programas de atividade física tem impacto positivo sobre doenças mentais, relacionadas a manifestações depressivas (NELSON et al, 2007).…”
Section: Discussionunclassified